The Similarities and Differences of Gender Bias in Indonesia and India. - Syarif, Jamal (Muadalah, 2022)
Indonesia and India have had a good relationship for a long time. Apart from the similarities mentioned in the previous paragraph, Indonesia and India also have other similarities. This project seeks to document gender bias in Indonesia and India.   A questionnaire comprising 43 questions was prepared to achieve the data.  There are two types of questions in the questionnaire, namely:  21 items with yes or no questions and 22 open questions. The result claimed that the stereotype is not a statement that justifies the opinion of everyone in Indonesia or in India. The statement is still valid in some parts of society. But the world is becoming more broadminded. The community's thinking about the rights and roles of each gender is being recognized. The people gradually are becoming aware of their respective roles and rights. The opportunity to gain higher education for all genders provides a great opportunity to minimize gender inequalities that are still felt by some particular people.